MyD88 Associated ROS Generation Is Crucial for Lactobacillus Induced IL-12 Production in Macrophage - Ichikawa, Shintaro; Miyake, Mika; Fujii, Rei; Konishi, Yutaka (PLOS ONE, 2012)
It is well known that some strains of lactic acid bacteria (LAB) can induce IL-12 which plays an important role in modulating immune responses. However, the mechanisms by which LAB induce IL-12 production remain unclear. Here, we examine the role of toll-like receptors (TLR's) and reactive oxygen species (ROS) in IL-12 production by LAB stimulated peritoneal macrophages. Our results indicate that a TLR is not necessary for IL-12 induction by LAB, whilst the universal adaptor protein, MyD88, is essential. Specific strains of LAB induced ROS that correlated with both the frequency of phagocytosis and IL-12 production. Reduction in IL-12 production by NADPH oxidase inhibitors or ROS scavengers demonstrates the crucial role of ROS in IL-12 induction. Interestingly, deficiency of TLR2, 4, 9 or MyD88 did not affect the phagocytosis of LAB strain KW3110, a potent IL-12 inducer, and ROS production was significantly reduced only in MyD88 deficient macrophages. These results suggest the existence of TLR-MyD88 independent LAB recognition and MyD88 related ROS induction mechanisms. We show here the importance of ROS for IL-12 induction and provide new insights into IL-12 induction by LAB.